Business to Business (B2b) Marketing Strategy for Construction Industry Equipment Manufacturing Company, CV. Ziaulhaq Solution - Tsany Zia Ulhaq (PT. Publikasiku Academic Solution, 2025)
The construction industry in Indonesia drives economic growth through large-scale infrastructure projects, increasing demand for reliable testing equipment like CV. Ziaulhaq Solution’s Laboratory Test Sieve. Despite robust production capabilities of 1,254 units per month, the company faces challenges due to reliance on offline distribution and intensifying market competition. The purpose of this study is to identify and analyze the challenges faced by the company in the face of intensifying market competition and shifting buyer behavior towards digital platforms. This research used qualitative methods, data was collected through in-depth interviews, document analysis, and triangulation. Tools such as PESTEL, 7P Marketing Mix, STP analysis, SWOT, and TOWS Matrix assessed market dynamics and strategic positioning. Findings highlight the integration of offline channels with digital strategies, including e-catalog registration for government procurement, improved after-sales service, and partnerships with educational institutions. Digital promotion through social media, value-based pricing, and certification for compliance are essential. This study provides actionable insights for manufacturers to align marketing efforts with decision-making processes, improving market competitiveness and customer trust. By combining traditional and digital approaches, CV. Ziaulhaq Solution can meet industry demands, achieve sustainable growth, and create longterm value for customers.